Modelling biomedical signals : (World Scientific, 2002)
Proceedings of the conference held September 19-21, 2001 in Bari, Italy. This book, a result of cross-disciplinary interaction among physicists biologists and physicians, covers several topics where methods and approaches rooted in physics are successfully applied to analyze and to model biomedical data.